“Hi! My name is Pauline, but most of my friends just call me Paul”: Divine on stage - Jean DU VERGER (E-REA)
The infamous star of John Waters’ underground movies, Divine (Harris Glenn Milstead), had become during the 1970s and 1980s the cross-dressing icon of a generation. His outrageous camp attire and acting skills contributed to the blurring of identity stability in a world where the sexual revolution of the late Sixties had already opened up a new frontier in terms of sexual practices and contributed to the gay and lesbian liberation. As Bernard Jay notes, the attraction of Divine lay in his colourful parody of rigid gender roles and conventional sexual morality. It is my intention to examine an aspect of Divine’s artistic career which is seldom explored by critics: his stage acting. The present paper will focus on the parts he played in two of Tom Eyen’s plays, while alluding to his roles in John Waters’ films. The present article will examine Divine’s performance in Women Behind Bars (1974) and The Neon Woman (1978), before considering the cultural rift which underpinned both plays. It will then try to assess the effect Divine had on his audiences in terms of gender stereotypes and gender perception. This paper contends that the different characters impersonated by Divine in his films tapped into Divine’s stage performances. These performances also shed light on what Marjorie Garber describes as the deconstructive nature of the transvestite performance that challenges the identity imposed upon one by society as it deconstructs gender by revealing its artificial nature.